A study of colour scheme of heritage shop houses, case study : Jalan Tunku Abdul Rahman, Kuala Lumpur / Nur Fisya Fishol Hamdi - Fishol Hamdi, Nur Fisya (2011)
In Malaysia, the scenario of appreciating and awareness towards heritage conservation was still lacking of support and guidance especially on the colour scheme for historical building. Looking the situation at Jalan Tunku Abdul Rahman with a colourful heritage shop houses and façade treatment decreasing original characteristic whereby every owner insisted to promote their commercial value rather than heritage value. Even though, heritage conservation field is still developing in our country and most of the shophouses is located at rapid development area, the owner and responsible authority failed to use the power of historic value to attract tourist and visitor instead of only thinked of economic value. Colour plays an important role whereby a right choice of colour scheme reflected and enhanced the ambience of character and also increased attractiveness. Colour is subjective, but in order to harmonize the area, an analysis should be done to identify suitable colour types for heritage building. Indirectly, it also involves public correspondence to strengthen the relationship with authority and consultant. It is important in a way to conserve our built environment of the place and hope this study will be an inspiration for conservation field to be closed to the community and at the same time can enable to produce a better future for historic building.